MERAYAKAN KESATUAN GEREJA DALAM KOMUNIO TUBUH DAN DARAH KRISTUS Celebrate The Unity Of The Church In The Communion Of The Body And Blood Of Christ - Rahawarin, Bernard A; Firmanto, Antonius Denny (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2021)
Unity is rightfully regarded as something that is important and essential in man’s life. In Christian life, in the context of God’s work of salvation, unity with Christ is of paramount importance. Unity with Christ constitutes the identity of those who have received the Sacrament of Baptism. That is why time and again the unity with Christ is being celebrated in the Eucharist by those who have been baptized. As the Sacrament of unity, the Eucharist unites us with Christ and with our neighbour. Bread and wine, which are offered during the Eucharist, are a sacrifice by the power of the Holy Spirit in order to create the One Church in Christ and in his Paschal Mystery. Seeing how important the celebration of the Eucharist is as a source of inspiration for the communion of life of the faithful, so this paper aims to describe how communion is celebrated in the celebration of the Eucharist together with proposed pastoral steps in the context of following up the fellowship in daily life. This paper uses a literature review with a descriptive-pastoral analysis method. Thrugh this way, the study is presented descriptively, accompanied by proposals for unity models as an aid for efforts to implement communio in daily life. Keywords: Unity; Communio, Body and Blood of Christ